2009
DOI: 10.1002/masy.200950123
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Polymerization in Ionic Liquids – Solvent Influence of New Dimension

Abstract: For the free radical polymerization of polar monomers which are soluble in ionic liquids (ILs) an extraordinary strong solvent effect can be observed. The solvent influence of the ILs leads to a strong enhancement of the polymerization rate and extremely high, mostly broadly distributed molecular weights. The experimentally determined very high propagation rate coefficient kp and the reduction of the activation energy of propagation EA can be explained by H‐bonds between both the monomer molecules and the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Regarding the use of RTILs as solvents in polymerization processes to replace the conventional organic solvents, although their use in free radical polymerization is still limited, they have shown some advantages such as higher polymerization rates and molecular weights than those obtained with traditional solvents such as toluene, tetrahydrofuran, among others. This behavior has been associated to a significant increase in the ratio: propagation rate constant /termination rate constant (k p /k t ), compared to polymerizations carried out in other polar solvents (Benton and Brazel, 2004;Li et al, 2006;Schmidt-Naake et al, 2008;Schmidt-Naake et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Regarding the use of RTILs as solvents in polymerization processes to replace the conventional organic solvents, although their use in free radical polymerization is still limited, they have shown some advantages such as higher polymerization rates and molecular weights than those obtained with traditional solvents such as toluene, tetrahydrofuran, among others. This behavior has been associated to a significant increase in the ratio: propagation rate constant /termination rate constant (k p /k t ), compared to polymerizations carried out in other polar solvents (Benton and Brazel, 2004;Li et al, 2006;Schmidt-Naake et al, 2008;Schmidt-Naake et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Interest in the use of these low‐melting ( T m < 100 °C), primarily organic salts stems from their unique properties such as a negligible vapor pressure and a high degree of thermal stability that have lead them to be proposed as alternatives to conventional solvents in a variety of processes . Thermally initiated radical polymerizations of methyl methacrylate (MMA) were some of the first polymerization reactions studied in IL solvents (e.g., 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([C 4 mim][PF 6 ]), and the kinetics of these processes have been extensively investigated for a variety of other monomers and methods of polymerization . Analysis of the rate of propagation ( R p ) using pulsed laser polymerization (PLP) and size exclusion chromatography (SEC) has generally indicated that IL solvation increases propagation rate constants ( k p ) .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The increasing interest in ILs as reaction media 9 and electrolytes [10][11][12] is due to their unique properties (for example, nonvolatility, nonflammability, high ionic conductivity and good thermal and electrochemical stability) and to the peculiarities of the chemical reactions performed in ILs. 1,9,13 In comparison with common organic solvents, ILs have high polarities and viscosities, 9 and thus they accelerate the free radical polymerization of unsaturated monomers and support the formation of polymers with ultra-high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][14][15][16][17] The influence of ILs on the kinetics of polymerization processes is related to the decrease in the activation energy 5,18,19 and the respective increase in the propagation rate. 4,5,[18][19][20][21][22] At the same time, the rate of termination decreases, 4,5,20,22,23 sometimes even by an order of magnitude, with the increase of IL concentration. 18 The increase in the propagation rate is generally attributed to the increased polarity of the ionic medium in comparison with that of the organic solvents that are traditionally used, whereas the decrease in the termination rate is assumed to be due to the increased viscosity of ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation